Detailed chemical abundances of several CP-stars of the upper main sequence - Gopka, V.F.; Yushchenko, A.V.; Shavrina, A.V.; Musaev, F.A. (Кинематика и физика небесных тел, 2005)
We present a study of the chemical composition of atmospheres of five stars of the upper main sequence. Investigations of the SB2 system 66 Eri permit to find the gallium spots in atmospheres of the components, the secondary component of the system is a HgMn star, the primary can also be a HgMn star with less pronounced anomalies. The components of the double system HD153720 appear to be metallic-lined stars. A review of studies of the abundance of SB2 systems with A4–F1 components shows that the usually accepted fraction of stars with the solar chemical composition in this region of the HR diagram can be decreased. The abundance patterns of Sirius (>50 elements) in the region of heavy elements give us additional arguments for the hypothesis that not only a diffusion is responsible for the overabundances of these elements in Sirius. The abundance pattern of δ Sct (49 elements) appears to be similar to δ Del type stars, maybe, a subtype of the prototype of one of the largest class of pulsating variables should be changed. The abundance pattern of the Przybylski’s star is the best stellar abundance pattern (after that of the Sun). The possible identification of radioactive elements (84 ≤ Z ≤ 99) in the atmosphere of the Przybylski’s star needs abundance determinations and can be the clue to the understanding of the nature of all CP stars.